Autologous, allogeneic hematopoietic cell transplantation and CAR-T/NK therapy: what is their real importance in PTCL? - Couto, Samuel C. F.; Kowes, Ariel; Aurabi, Camila S.; Oliveira, Theo G. M.; Klinger, Paulo; Rocha, Vanderson (Frontiers in Oncology, 2023)
Peripheral T cell lymphoma (PTCL) is a rare and aggressive type of non-Hodgkin's lymphoma that affects mature T cells. This type of cancer is characterized by the abnormal growth of T cells, which can accumulate in the lymph nodes, spleen, bone marrow, and other organs, leading to a variety of symptoms. PTCLs are often difficult to diagnose and treat, and they have a poorer prognosis than other types of lymphoma. However, recent advancements in treatment options, such as targeted therapies have shown promise in improving outcomes for patients with PTCL. Here, we discuss the use of autologous and allogeneic hematopoietic cell transplantation (HCT) as a treatment strategy for patients with PTCL, as well as the recent treatment approaches based on advanced cellular therapy. The current evidence for the use of HCT in PTCL is mainly derived from registry data, retrospective studies, and expert opinion, as randomized trials are limited due to the low incidence and histological heterogeneity of PTCL subtypes.